Failure through crack propagation in components with holes and notches: An experimental assessment of the phase field model. (5th December 2022) - Cavuoto, R.; Lenarda, P.; Misseroni, D.; Paggi, M.; Bigoni, D.
Abstract: Fracture growth in a material is strongly influenced by the presence of inhomogeneities, which deviate crack trajectories from rectilinearity and deeply affect failure. Increasing crack tortuosity is connected to enhancement of fracture toughness, while often a crack may even be stopped when it impinges a void, which releases the stress concentration. Therefore, the determination of crack trajectories is important in the design against failure of materials and mechanical components. The recently developed phase-field approach (AT1 and AT2 models), based on a variational approach to damage localization, is believed to be particularly suited to describe complex crack trajectories. This belief is examined through a comparison between simulations and photoelastic experiments on PMMA plates, which have been designed in a new way, to highlight the effects of notches and circular holes on fracture propagation. The latter is shown to initiate from a notch and to be strongly attracted by voids. When a void is hit, fracture is arrested, unless the void contains a notch on its internal surface, from which a new crack nucleates and propagates. Different mechanical models are tested where fracture initiates and grows (i.) under Mode I compact tension, (ii.) four-point bending and (iii.) a tensile stress indirectly generated during compression of samples containing a circular hole. The experiments show that the fracture propagation may be 'designed' to develop in different tortuous paths, involving multiple arrests and secondary nucleation. Simulations performed with an ad hoc implemented version of the AT1 and AT2 phase-field methods (equipped with spectral decomposition, in which a crack is simulated as a highly localized zone of damage accumulation) are shown to be in close agreement with experiments and therefore confirm the validity of the approach and its potentialities for mechanical design.